1926 Miss. Laws 272 - (:unkn) unknown (My University, 1926)
Ch. 176, §§ 1-2: [A]ny person, who, with intent to commit crime, breaks and enters, either by day or by night, any building, whether inhabited or not, and opens or attempts to open any vault, safe or other secure place by the use of nitroglycerine, dynamite, gunpowder or any other explosive, shall be deemed guilty of burglary with explosives. § 2. Any person duly convicted of burglary with explosives shall be punished by imprisonment for a term of not less than twenty-five nor more than forty years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME